Piano in the intonation process of tonally unstable and non-tonal melodies in teaching Solfège - Vidicki Elizabeta (Zbornik Radova Akademije Umetnosti, 2015)
The question of utilising the piano from the aspect of Solfège teaching methodology is indeed a relevant one. Since the piano is present in almost all music activities, whether it is used as a primary source of sound, i.e. as a harmonic accompaniment to vocal reproduction, or in any other activity, the use of this musical instrument should be approached with great consideration, and methodologically correct. In practising tonally unstable and non-tonal melodies, piano, as a teaching tool, is primarily used as piano accompaniment, i.e. as chord support. Thus, it is important to consider the situations, ways and aims of the use of piano, as well as to point to certain aspects relevant to understanding and accurate voicing of these types of melody.